Guide to GATT law and practice : analytical index (World Trade Organization GenevaCH, 1995)
Presents a guide to the legal interpretation and application of the General Agreement, and a repertoire of GATT practice and drafting history, including decisions, panel reports and discussions between contracting parties.
Contents: v.1. Articles i-xxi. -v.2. Articles xxii-xxxviii